Pengaruh Brand Ambassador Dan Korean Wave Terhadap Minat Beli Pada Marketplace Tokopedia di Kabupaten Karawang - Sevtiani, Novia; Hermana, Cecep (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to analyze the influence of Brand Ambassadors and the Korean Wave on Purchase Intention at the Tokopedia marketplace in the Karawang district. The research employed a quantitative approach, utilizing purposive sampling as the nonprobability sampling technique. The sample in this study consisted of 97 respondents who are Tokopedia users in the Karawang district. The results of this research show that Brand Ambassadors influence Purchase Intention, while the Korean Wave does not have an influence on Purchase Intention. Furthermore, both Brand Ambassadors and the Korean Wave collectively influence Purchase Intention.